2020
DOI: 10.1177/0194599820934380
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and Oral Manifestations of COVID‐19: Sex‐Related Symptoms—A Potential Pathway to Early Diagnosis

Abstract: Objective The coronavirus disease 2019 (COVID-19) pandemic poses a threat to global health. Early diagnosis is an essential key to limit the outbreak of the virus. Study Design Case series, study conducted between March 25, 2020, and April 15, 2020. Setting Ambulatory, nonhospitalized patients who were quarantined in a designated hotel for COVID-19 patients and were recruited by an advertisement at the hotel. Subjects and Methods In total, 140 patients participated in a web-based questionnaire assessing initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
219
4
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(257 citation statements)
references
References 30 publications
10
219
4
24
Order By: Relevance
“…We identified 2 meta-analyses of 24 and 21 studies/case reports respectively that described patients with olfactory/ gustatory dysfunction [69,70]. In addition, we describe 11 studies that evaluated olfactory/gustatory dysfunction in COVID-19 patients (Table 6) [71][72][73][74][75][76][77][78][79][80][81].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2 meta-analyses of 24 and 21 studies/case reports respectively that described patients with olfactory/ gustatory dysfunction [69,70]. In addition, we describe 11 studies that evaluated olfactory/gustatory dysfunction in COVID-19 patients (Table 6) [71][72][73][74][75][76][77][78][79][80][81].…”
Section: Search Resultsmentioning
confidence: 99%
“…They found that the use of intranasal or oral steroids enhanced the recovery of COVID-19related olfactory/gustatory dysfunction [70]. We found 11 studies that specifically evaluated gustatory and olfactory functions in patients with COVID-19 infection [71][72][73][74][75][76][77][78][79][80][81]. Majority of patients had olfactory/gustatory dysfunction in addition to other symptoms like fever, cough, sore throat, and headache.…”
Section: Olfactory and Gustatory Dysfunctionmentioning
confidence: 95%
“… 11. Summary item on the overall risk of study bias Altin, 2020 [ 45 ] 0 1 1 1 1 1 0 1 1 1 Low 8 Barillari, 2020 [ 46 ] 1 1 0 0 1 1 0 1 1 1 Moderate 7 Beltrán-Corbellini, 2020 [ 47 ] 0 1 0 1 1 1 0 1 1 1 Low 7 Bénézit, 2020 [ 27 ] 0 1 1 0 1 1 0 1 1 1 Moderate 7 Biadsee, 2020 [ 48 ] 0 0 0 0 1 1 0 1 1 1 High 5 Brandstetter, 2020 [ 28 ] 0 1 1 1 1 1 0 1 1 1 Low 8 Carignan, 2020 [ 29 ] 0 1 1 1 1 1 0 1 1 1 …”
Section: Resultsmentioning
confidence: 99%
“…This was followed by dysgeusia which was reported by 54.3% ( n = 76) of patients, and xerostomia reported by 51.4% ( n = 72) patients. The onset time for dysgeusia and xerostomia was not recorded [ 16 ]. Another study investigated ear, nose and throat symptoms in a cohort of 50 patients affected by COVID-19 using a standardized questionnaire that assessed olfactory, gustatory, and auditory data, as well as xerostomia and eye dryness.…”
Section: Discussionmentioning
confidence: 99%